INTERVENTION OF RARELY SEEN CATHETER LOSS DURING PERMANENT TUNNELED HEMODIALYSIS CATHETERIZATION: A CASE REPORT - Emced Khalil (Sanamed, 2020)
Introduction: In patients with end-stage renal disease (ESRD), permanent hemodialysis cathetersare often used by performing percutaneous catheterization to create a permanent vascular access. To the best of our knowledge, no cases with accidental loss of catheter piece during hemodialysis catheter replacement or during its retrieval under scopy has been reported in the literature yet.